Mice with sclerostin gene deletion are resistant to the severe sublesional bone loss induced by spinal cord injury. Issue 12 (December 2016) - Qin, W.; Zhao, W.; Li, X.; Peng, Y.; Harlow, L.; Li, J.; Qin, Y.; Pan, J.; Wu, Y.; Ran, L.; Ke, H.; Cardozo, C.; et al.
Abstract Summary Bone loss after spinal cord injury (SCI) is rapid, severe, and refractory to interventions studied to date. Mice with sclerostin gene deletion are resistant to the severe sublesional bone loss induced by SCI, further indicating pharmacological inhibition of sclerostin may represent a promising novel approach to this challenging medical problem. Introduction The bone loss secondary to spinal cord injury (SCI) is associated with several unique pathological features, including the permanent immobilization, neurological dysfunction, and systemic hormonal alternations. It remains unclear how these complex pathophysiological changes are linked to molecular alterations that influence bone metabolism in SCI. Sclerostin is a key negative regulator of bone formation and bone mass. We hypothesized that sclerostin could function as a major mediator of bone loss following SCI. Methods To test this hypothesis, 10-week-old female sclerostin knockout (SOST KO) and wild type (WT) mice underwent complete spinal cord transection or laminectomy (Sham). Results At 8 weeks after SCI, substantial loss of bone mineral density was observed at the distal femur and proximal tibia in WT mice but not inSOST KO mice. By μCT, trabecular bone volume of the distal femur was markedly decreased by 64 % in WT mice after SCI. In striking contrast, there was no significant reduction of bone volume inSOST KO/SCI mice compared withSOST KO/sham. Histomorphometric analysis of trabecular bone revealed that the significant reduction in bone formation rate following SCI was observed in WT mice but not inSOST KO mice. Moreover, SCI did not alter osteoblastogenesis of marrow stromal cells inSOST KO mice. Conclusion Our findings demonstrate thatSOST KO mice were protected from the major sublesional bone loss that invariably follows SCI. The evidence indicates that sclerostin is an important mediator of the marked sublesional bone loss after SCI, and that pharmacological inhibition of sclerostin may represent a promising novel approach to this challenging clinical problem.